Manifestations of religious dialogue between Muslims and Jews: Secular Jews as a model - Al-Shamari, Maha Dahawi (Arab Journal for Sciences and Research Publishing, 2023)
This study seeks to reveal the appearance and manifestations of religious dialogue between Muslims and secular Jews by addressing their prominent beliefs and their compatibility with their counterparts in the Islamic religion; considering the importance of being enlightened with the beliefs of others in establishing religious dialogue. During monitoring the most important appearances and manifestations of the religious dialogue at the cultural level between Muslims and secular Jews. This research follows the inductive approach to the collection of data based on the doctrine of secular Jews. As well as the historical approach in the statement of the conversions of religious thought of Jews adopted description and comparison in the analysis of the mosques and differences between Islamic religion and Jewish religion (secular division).Study founding: - The initial ground for dialogue between Judaism and Islam was founded by the Holy Quran and reinforced by Muslims' historical cultural experience.- No real dialogue will take place for Muslims with Jews in general, especially those who are secular. Without the Islamic nation meeting again as a strong unit - similarly to the days of the Messenger and the Caliphs - capable of confronting the other and dialogue with them
Keywords: Dialogue; Jews; Islam; Holy Qur’an; secularism; normalization